PENGARUH KEBIJAKAN UTANG, LIKUIDITAS DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN JASA KONSTRUKSI MILIK NEGARA DAN PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2014 - Malvino Silitonga, Bambang Widarno & Fadjar Harimurti (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this study is to find the influence of policy debt, liquidity and profitability on the company. The independent variable from thy study is policies debt, liquidity, profitability and dependent variable of study is value of company. Population in research this is a company construction services belonging to a country and telecommunication companies enrolled in BEI the periode 2009-2014. A method of the sample used is purposive sampling. Sample in this research that is by using software SPSS 18. The calculation on show that the policies debt have a negative influence significant impact on value of enterprise, while liquidity and profitability do not affect significant impact on value of enterprise.Keywords: value of company, policies debt, liquidity, profitability.